Indigenous Yeast Interactions in Dual-Starter Fermentations May Improve the Varietal Expression of Moschofilero Wine - Nisiotou, Aspasia; Mallouchos, Athanasios; Tassou, Chrysoula; Banilas, Georgios (Frontiers in Microbiology, 2019)
Μulti-starter wine fermentations employing non-Saccharomyces (NS) yeasts are becoming an emerging trend in winemaking. It is therefore important to determine the impacts of different NS strains in the wine phenotype and in particular the aroma outputs in different inoculation schemes and fermentation conditions. Here, two native NS yeasts, Lachancea thermotolerans LtMM7 and Hanseniaspora uvarum HuMM19, were assessed for their ability to improve the quality of Moschofilero, a Greek aromatic white wine. The NS strains were initially examined in laboratory scale fermentations in mixed inoculations with ScMM23, a native Saccharomyces cerevisiae strain. LtMM7 was selected to be further evaluated in pilot scale fermentations. Five different inoculation schemes were considered: single inoculation of ScMM23 (IS), simultaneous inoculation of ScMM23 with HuMM19 (SMH) or LtMM7 (SML), and sequential inoculation of HuMM19 (SQH) or LtMM7 (SQL) followed by ScMM23 . At laboratory scale fermentations, the chemical profiles were largely affected by both the NS species and the inoculation scheme applied. The sequential inoculation using HuMM19 produced the most divergent wine phenotype. However, HuMM19 caused significant increases in acetic acid and ethyl acetate levels that impeded its use in pilot scale trials. LtMM7 significantly affected the chemical profiles of wines produced at the winery, especially in the sequential inoculation scheme. Importantly, LtMM7 significantly increased the levels of acetate esters or ethyl esters, depending on the inoculation method applied. In particular, acetate esters like isobutyl acetate, hexyl acetate, and 2-phenylethyl acetate, which all impart fruity or floral aromas, were significantly increased in SQL. On the other hand, higher levels of total ethyl esters were associated with SML. The most striking differences were observed in the levels of fruit-impair esters like ethyl decanoate, 3-methylbutyl octanoate, and isoamyl hexanoate. This is the first study to report a significant increase in the ethyl ester fraction by L. thermotolerans. Interestingly, L. thermotolerans in SQL also increased the concentrations of damascenone and geraniol, the major teprenic compound of Moschofilero, which are associated with several typical floral and fruity aromas of the variety. Present results show that L. thermotolerans may enhance the varietal character and increase the chemical complexity of Moschofilero wines.